2020
DOI: 10.1021/acsmacrolett.0c00298
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Site Selectivity of Perfluoropyridine for Facile Access to Densified Polyarylene Networks for Carbon-Rich Materials

Abstract: Fluorinated molecules containing reactive functionalities are of great interest to the materials community as these compounds can be used to prepare fluorinated polymers with desirable physical and electronic properties. Despite their potential, many of these compounds are limited by their synthesis which generally requires transition-metal-catalyzed coupling reactions or harsh fluorinating conditions. Perfluoroheteroaromatic compounds provide a unique solution to this problem as compounds such as perfluoropyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…At around the same time, Houck et al reported the synthesis of two highly soluble high aromatic content (HAC) perflfluoropyridine-based thermosetting precursors [ 70 ]. Previously, to obtain polymers or materials that contain HAC, transition-metal-catalyzed coupling or harsh fluorination methods were required.…”
Section: Perfluoropyridine Used In Polymers and Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…At around the same time, Houck et al reported the synthesis of two highly soluble high aromatic content (HAC) perflfluoropyridine-based thermosetting precursors [ 70 ]. Previously, to obtain polymers or materials that contain HAC, transition-metal-catalyzed coupling or harsh fluorination methods were required.…”
Section: Perfluoropyridine Used In Polymers and Materialsmentioning
confidence: 99%
“…Initially, regioselective nucleophilic addition takes place with PFPy by first reacting it with lithiated 1,2-diphenylethyne or anthracene at the 4-position, to generate compounds 20 and 21 , respectively. To complete the monomers, further reactions are accomplished at both the 2 and 6-position by lithiated 1,2-diphenylethyne to generate monomers 22 and 23 , respectively ( Scheme 19 ) [ 70 ].…”
Section: Perfluoropyridine Used In Polymers and Materialsmentioning
confidence: 99%
See 3 more Smart Citations